Can Anal Cytology Be a Tool in Following Patients Treated for Squamous Cell Carcinoma of the Anus?. Issue 7 (July 2022) - Brasseur, Benjamin; Subillaga, Oswaldo; Vrees, Matthew; Klipfel, Adam; Roth, Leslie; Schechter, Steven
Background: Squamous cell carcinoma of the anus (SCCA) is associated with human papillomavirus infection and preceded by high-grade squamous intraepithelial lesions (HSIL). Following successful treatment, the standard of care is to surveille for local recurrence with both anoscopy and digital rectal examination. While high-resolution anoscopy (HRA) has been shown to identify HSIL during the surveillance period, it requires specialized training and resources. 1 The burden of these resources may be reduced by conducting surveillance with anal cytology. We studied 2 questions: (1) Can anal cytology identify HSIL in patients after successful treatment of SCCA? (2) Can HSIL be found with anal cytology after completion of chemoradiation for SCCA? Methods: Patient charts were queried for diagnosis of SCCA. Patients were excluded if they were not successfully treated for cure or if patients had not been seen in the surveillance period of 5 years following treatment. Descriptive statistics were elucidated. Results: 104 patient charts met inclusion criteria. 81 were surveilled using standard of care, while 23 were followed with standard of care plus anal cytology. 5 patients followed with cytology demonstrated HSIL. 2/5 were found via cytology, 1/5 via HRA, and 2/5 patients via exam under anesthesia and biopsy. Discussion: This study demonstrated that HSIL was identified cytologically in the surveillance period. There may be utility in using anal cytology to identify HSIL in patients during this period in lieu of the specialized resources required for HRA. This may allow dysplasia to be treated with excision and fulguration prior to redevelopment of SCCA.